Feasibility Analysis of an E-Magazine on Conventional Biotechnology Subtopic Based on Proximate Analysis Results of Cincalok Fermentation - Filardha Azelia Vallahayil; Anisyah Yuniarti; Laili Fitri Yeni (Jurnal Penelitian Pendidikan IPA, 2025)
The E-magazine is an innovative, technology-based learning media that is expected to enhance the effectiveness of Biology education. This study aims to develop and analyze the feasibility of an e-magazine on conventional biotechnology based on the proximate analysis of cincalok fermentation. This research employed the Research and Development (R&D) method, involving stages of proximate analysis, design, development, and validation. The proximate analysis of cincalok revealed a moisture content of 8.88%, ash 11.30%, fat 4.35%, protein 35.27%, and carbohydrate 40.20%. These factual data were integrated as the scientific content of the e-magazine to provide contextual learning materials. Validation by five experts yielded a Content Validity Ratio (CVR) of 1.00 and a Content Validity Index (CVI) of 1.00 across all aspects, including format, content, and language. Based on these results, the e-magazine is concluded to be a highly valid and feasible digital learning medium. This media serves as a scientifically-grounded resource to support biotechnology education by utilizing local potential.